An Open-Label Study of an Herbal Topical Medication (QoolSkin) for Patients with Chronic Plaque Psoriasis - Arnon D. Cohen; Raquel Shalev; Ron Yaniv; Avner Shemer (The Scientific World Journal, 2007)
QoolSkin is novel herbal topical medication indicated for the treatment of patients with psoriasis and we endeavored to determine the efficacy of QoolSkin in patients with chronic plaque psoriasis. In an open-label, parallel-group study conducted at four sites in Israel, patients with chronic plaque psoriasis were treated by application of QoolSkin two to three times per day, for a period of 16 weeks. Clinical assessment was performed using the Psoriasis Area and Severity Index (PASI) and the Beer-Sheva Psoriasis Severity Score (BPSS). The study included 100 patients (48 men, 52 women; age 18–65 years). QoolSkin was well tolerated and there were no local or systemic side effects. There was a 19% reduction in PASI, from a mean of 9.8 ± 9.5 before treatment to 8.0 ± 9.6 after treatment (p = 0.09). There was a 20% reduction in BPSS, from a mean of 16.1 ± 9.8 before treatment to 12.8 ± 10.6 after treatment (p = 0.01). The reduction in PASI and BPSS was pronounced in women (32 and 31%, respectively) as compared to men (9 and 11%, respectively). The reduction in PASI and BPSS was parallel to the length of time the patients were treated by QoolSkin. In patients treated by one of the investigators, who applied QoolSkin three times per day and for a long period of time (mean 101.1 days), the reduction in PASI was 32.0% and the reduction in BPSS was 37.8%. In patients with chronic plaque psoriasis, QoolSkin treatment was well tolerated. Application of QoolSkin was associated with a decrease in disease severity, as assessed by the patients and physicians. Application of QoolSkin three times per day for long period is associated with a better response to treatment.